Study on the causal relationship and optimise the extraction procedure of herbal preparation from Herba Mimosae pudicae, Folium Erythrinae variegatae, Cortex Cinnamomi iners and Herba et radix Scopariae - Oanh - Hoang Hua; Van- Thi- Thanh Nguyen; Nam- Van- Ho Phan; Kiet- Khang Chung; Quyen- Hong- To Duong (Vietnam Journal of Science, Technology and Engineering)
Herbal preparations from four herbs - Mimosa pudica, Erythrina variegata, Scoparia dulcis, and Cinnamomum iners - exhibit sedative effects, treat insomnia, and effectively reduce anxiety and depression. The chemical components present in these medicinal herbs, such as mimosine and coixol, are biologically active substances. This study investigates the causal relationship and optimises the extraction procedure to achieve higher extraction efficiency. Fourteen experiments were designed using DesignExpert software to evaluate the influence of three independent variables (number of extractions, extraction time, and solvent-to-material ratio) on four dependent variables (extraction efficiency of mimosine, extraction efficiency of coixol, total extraction efficiency, and production cost). The content of mimosine and coixol was determined using the high-performance liquid chromatography (HPLC) method. Data were utilised as input for Phasolpro RD 1.0 software to model and optimise the extraction procedure for the medicinal herbs in the formulation. The extraction process was optimised with a solvent-to-material ratio of 21:1, two extractions, and an extraction time of 2.03 hours. The optimised procedure provides a critical foundation for improving extract quality and applying it as a semi-finished material for medicinal product production.